Statistik Perkahwinan Tanpa Kebenaran Kelantan 2019-2023: Satu Analisis - Ahmad Syakir Mohd Nassuruddin; Mohd Zain Mubarak; Zulfaqar Mamat; Muhammad Adam Abd Azid; Mohammad Jawwad Md Yusnan (Usuli Faqih Research Centre PLT, 2024)
Indexed by MyCite